Factor Analysis Model for Diagnostic Assessment and Instructional Approaches in Ghana’s New Curriculum: The Case of Differentiation, Scaffolding and Inclusion - Bosson-Amedenu Senyefia; Osei-Asibey Eunice; Otoo Henry (Archives of Current Research International, 2020)
Ghana’s new Basic Education Curriculum emphasizes on ensuring that every learner benefits from the teaching and learning process. The study used the survey research design aimed at determining the predictive power with which use of Scaffolding, Differentiated techniques and Inclusion approaches predict diagnostic assessment. The features, strategies and principles underpinning instructional Scaffolding, Differentiation and Inclusion approaches as well as Diagnostic assessment formed the basis of the construction of 14 text items used in the questionnaire in this study. The study involved a population of 132 basic school teachers from sixteen (16) regions of Ghana. A sample size of 100 was computed at 95% confidence interval and randomly selected from the population. The reliability of the items was assessed with Cronbach’s Alpha (0.976). Bartlett’s test of sphericity was statistically significant (P< 0.01, Chi-square =3077.529, DF=91), and the KMO statistic was 0.924. All multiple extraction approaches such as Parallel analysis, Kaiser’s criterion and Scree test suggested retaining two factors. Varimax rotated matrix was used to generate factor scores for modeling the relationships between diagnostic assessment and inclusion, differentiated techniques as well as Scaffolding using multiple linear regressions. From the results, Scaffolding (B1 = .744, B2 =.185, F= 466.442, P<0.001), Differentiated approaches (B1 = .516, B2 =.400, F=312.809, P<0.001) and Inclusion (B1 =.512, B2 =.373, F= 213.375, P<0.001) pedagogical approaches were statistically significant and positively related to diagnostic assessment. Scaffolding, Differentiated approaches and Inclusion approaches were found to have predictive power of 91%, 87% and 82% respectively. Instructional Scaffolding was found to be the most efficient predictor of diagnostic assessment. This study provides scientific evidence that the Scaffolding, Inclusion and Differentiated techniques outlined in Ghana’s new Curriculum provides sufficiently for Diagnostic assessment although it was not explicitly stated in it. It is therefore recommended for Ghana Education service to run a continuous training programme for teachers in efficient use of these techniques for effective teaching and learning.